Homology Modeling dan Molecular Docking Senyawa Aktif dari Bengkoang (Pachyrrhizus erosus) sebagai Inhibitor Tirosinase pada Homo sapiens - ENDANG LUKITANINGSIH; ANNY A. MUSTIKAWATY; ARI SUDARMANTO (JURNAL ILMU KEFARMASIAN INDONESIA, 2013)
One mechanism of whitening agent is to inhibit the tyrosinase enzyme in melanogenesis process. However, since the human tyrosinase has not been determinated experimentally, therefore research on human tyrosinase can not be conducted. Homology modeling is one method that can be used to exhibit the three-dimensional structure of human tyrosinase. This model used to predict the interaction of bengkoang (Pachyrrhizus erosus) active compounds with the human tyrosinase enzyme by using a molecular docking approach (pose analysis). In addition, the strength of the bond between the ligand compounds and the site protein target can be predicted by analyzing the resulting score. Homology modeling was carried out using Amber99 method of software MOE 2009.10 and Bacillus megaterium (TyrBm) as a template. The model obtained was evaluated using Ramachandran plot analysis, z-score, and the plot energy ProSA. The best model used for molecular docking using the active site ligand, ALPHA PMI placement method, and affinity DG scoring of MOE 2009.10 software. The best model is the TyrHSM (MOE default alignment) with 96.7% residues are in allowed regions of the Ramachandran plot, has the least positive region, and has a z-score ratio> 1. The isolated compound 2-butoxy-2,5-bis (hydroxymethyl)-tetrahydrofurane-3,4-diol is predicted have the best affinity to human tyrosinase with a score -0.3598 kcal/mol.